(untitled) (Research, Society and Development, 2021)
The 5S Program is a Quality Management program created in Japan and today known and used worldwide, including in Brazil, in order to generate improvements in the work environment. This work had as main objective to evaluat the efficiency of the implementation of the 5S Program in the Laboratory of Sensory Analysis and in the Pilot Plants of Meat and Fish, Bakery and of Dairy of the Federal Institute of Ceará – Campus Sobral. The implantation took place at the same time in the four laboratories and was divided in to three phases: Pre – implantation or initial phase, the bases for the implantation were defined; Implementation of the “5S”, the five senses of quality were applied; E Post – implementation or final phase, actions were taken to promote continuous improvement. In the initial diagnosis, pre – implantation phase, using a checklist, the laboratories presented the following complianse results: Sensory Analysis 46% (Regular), Meat and Fish 50% (Regular), Bakery 40% (Regular) and Dairy 38% (Insufficient). In the implementation phase of the “5S”, the results obtained were qualitative with regard to the environmental transformation generated. In the Final Evaluation, post – implantation phase, through the application of the same checklist, the laboratories presented the following complianse results: Sensory Analysis 90% (Good), Meat and Fish 86% (Good), Bakery 78% (Good) and Dairy 90% (Good). Through the evolution shown in the images and graphics, it is concluded that the 5S is na efficient program capable of generating significant improvements in the work environment.